Decolonization, popular song and Black-Pacific identity in Melanesia. (January 2020) - Webb, Michael; Webb-Gannon, Camellia Bell
Melanesians were pejoratively labelled the dark-skinned islanders by European explorers in the 1830s, an act that has shaped understandings of the region and its peoples down to the present day. In this brief essay, we attempt to demonstrate that since the new millennium, aided by digital tools and the Internet, young Melanesians have localized Black Atlantic music forms in order to assert agency, no matter how limited, in relation to their experiences of rejection and marginalization within the global system. The musical creation of new identity spaces is briefly considered through three condensed case studies that exemplify core contemporary Melanesian social concerns: (1) Pacific climate change, (2) Melanesian cultural identity in relation to pressures of modernity and globalization and (3) independence for West Papua. Increasingly, we propose, such expressions are becoming a significant factor in the ongoing reshaping in Melanesia of what it means to belong in the world while remaining culturally distinct.